Influence of mobile genetic elements and insertion sequences in long- and short-term adaptive processes of Acidithiobacillus ferrooxidans strains - Moya-Beltrán, Ana; Gajdosik, Martin; Rojas-Villalobos, Camila; Beard, Simón; Mandl, Martin; Silva-García, Danitza; Johnson, D Barrie; Ramirez, Pablo; Quatrini, Raquel; Kucera, Jiri (Scientific reports, 2023)
The recent revision of the Acidithiobacillia class using genomic taxonomy methods has shown that, in addition to the existence of previously unrecognized genera and species, some species of the class harbor levels of divergence that are congruent with ongoing differentiation processes. In this study, we have performed a subspecies-level analysis of sequenced strains of Acidithiobacillus ferrooxidans to prove the existence of distinct sublineages and identify the discriminant genomic/genetic characteristics linked to these sublineages, and to shed light on the processes driving such differentiation. Differences in the genomic relatedness metrics, levels of synteny, gene content, and both integrated and episomal mobile genetic elements (MGE) repertoires support the existence of two subspecies-level taxa within A. ferrooxidans. While sublineage 2A harbors a small plasmid related to pTF5, this episomal MGE is absent in sublineage 2B strains. Likewise, clear differences in the occurrence, coverage and conservation of integrated MGEs are apparent between sublineages. Differential MGE-associated gene cargo pertained to the functional categories of energy metabolism, ion transport, cell surface modification, and defense mechanisms. Inferred functional differences have the potential to impact long-term adaptive processes and may underpin the basis of the subspecies-level differentiation uncovered within A. ferrooxidans. Genome resequencing of iron- and sulfur-adapted cultures of a selected 2A sublineage strain (CCM 4253) showed that both episomal and large integrated MGEs are conserved over twenty generations in either growth condition. In turn, active insertion sequences profoundly impact short-term adaptive processes. The ISAfe1 element was found to be highly active in sublineage 2A strain CCM 4253. Phenotypic mutations caused by the transposition of ISAfe1 into the pstC2 encoding phosphate-transport system permease protein were detected in sulfur-adapted cultures and shown to impair growth on ferrous iron upon the switch of electron donor. The phenotypic manifestation of the △pstC2 mutation, such as a loss of the ability to oxidize ferrous iron, is likely related to the inability of the mutant to secure the phosphorous availability for electron transport-linked phosphorylation coupled to iron oxidation. Depletion of the transpositional △pstC2 mutation occurred concomitantly with a shortening of the iron-oxidation lag phase at later transfers on a ferrous iron-containing medium. Therefore, the pstII operon appears to play an essential role in A. ferrooxidans when cells oxidize ferrous iron. Results highlight the influence of insertion sequences and both integrated and episomal mobile genetic elements in the short- and long-term adaptive processes of A. ferrooxidans strains under changing growth conditions.
Keywords: síra; Iron; oxidace-redukce; železo; transpozibilní elementy DNA; Oxidation-Reduction; Sulfur; Acidithiobacillus; DNA Transposable Elements